2019
DOI: 10.1021/acs.jpcb.8b11458
|View full text |Cite
|
Sign up to set email alerts
|

Local and Global Electric Field Asymmetry in Photosynthetic Reaction Centers

Abstract: The origin of unidirectional electron transfer in photosynthetic reaction centers (RCs) has been widely discussed. Despite the high level of structural similarity between the two branches of pigments that participate in the initial electron transfer steps of photosynthesis, electron transfer only occurs along one branch. One possible explanation for this functional asymmetry is the differences in the electrostatic environment between the active and the inactive branches arising from the charges and dipoles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…2 and 4 ). However, the L/M residues that stabilize H L •– with respect to H M •– (e.g., Glu-L104 ( 39 ), SI Appendix , Table S5 ) do not correspond to those that stabilize Pheo D1 •– with respect to Pheo D2 •– ( Table 5 ), which implies the difference in the protein electrostatic environment and the charge-separation mechanism between the two reaction centers.…”
Section: Resultsmentioning
confidence: 99%
“…2 and 4 ). However, the L/M residues that stabilize H L •– with respect to H M •– (e.g., Glu-L104 ( 39 ), SI Appendix , Table S5 ) do not correspond to those that stabilize Pheo D1 •– with respect to Pheo D2 •– ( Table 5 ), which implies the difference in the protein electrostatic environment and the charge-separation mechanism between the two reaction centers.…”
Section: Resultsmentioning
confidence: 99%
“…They raise the question of whether coherence in the excited state can be functionally relevant or whether it is too fragile to be utilized in realistic photochemical transformations. The local asymmetry arising from local fields is at the core of the functional asymmetry of natural photosynthetic reaction centers 68 . It also explains the lack of success in the elaboration of symmetric molecular systems that could exhibit double excitedstate proton transfer [69][70][71] .…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42][43][44][45][46][47][48][49][50] Despite the pseudo-C 2 symmetric cofactor arrangement, the difference in the amino acid sequences between the L-and M-branches leads to the difference in the redox potentials of the pigments via electrostatic interactions and polarization. [51][52][53] A previous study using time-dependent density functional theory (TDDFT) with the quantum mechanics/molecular mechanics/polarizable continuum model (QM/MM/PCM) method indicated that the intermediate states of charge separation along the L-and M-branches, i.e., [P L P M ]c + B L c À and [P L P M ]c + B M c À , are lower and higher in energy than that of (P L P M )*, respectively. 34 In contrast to PbRC, the excitation energies of P D1 and P D2 in PSII are higher than those of Chl D1 and Chl D2 , 9,34 where the exciton tends to be localized on a single pigment owing to a weak excitonic coupling.…”
Section: Introductionmentioning
confidence: 99%